Industrial wastewater treatment and reuse: Heckman probit sample selection model - Urgessa Tilahun Bekabil; M.K. Jayamohan; Amsalu Bedemo Beyene (MethodsX, 2025)
Wastewater treatment and reuse help emerging economies to minimize their water scarcity. This study examines the factors influencing wastewater treatment and reuse by manufacturing firms in Shaggar City. The Heckman Probit Sample Selection model is used to analyse the data collected from 303 randomly selected manufacturing firms using structured questionnaires. Results revealed that R&D costs, innovation practices, the availability of purpose-driven vehicles for waste transport, energy costs, and the scale of operations significantly affect the reuse of treated wastewater. The result also shown that presence of wastewater treatment facilities, energy costs, R&D costs, and existence of solid waste disposal facilities were found to be statistically significant in determining wastewater treatment decision. The result implies that firms with treatment and disposal facilities take a more active approach to adopting sustainable techniques as their energy costs and R&D investment rise. Policymakers and industrial firms should think about ways to educate and encourage firms and the surrounding community to reuse treated wastewater, which promotes water conservation and reduces urban water scarcity. • The Heckman Probit Selection model effectively identifies and analyzes the factors influencing wastewater treatment and reuse in the industrial sector. • Implementing wastewater treatment solutions is crucial for minimizing water shortages in urban areas of emerging economies. • The estimated model highlights the essential actions to be taken for achieving a sustainable environment.